Didactic Unit:: the teaching of organizational control - Rodríguez García, Dora Marcela; Universidad Pedagógica y Tecnológica de Colombia; Díaz Aldana, Ana Patricia; Universidad Pedagógica y Tecnológica de Colombia (UPTC Editorial, 2023)
Didactic Unit: the teaching of organizational control, is the result of the research project with SGI 2753 entitled “Didactics of the social sciences”, which was obtained through an interdisciplinary effort that contributes to the training processes of the Public Accounting and Business Administration programs of the Universidad Pedagógica y Tecnológica de Colombia, Chiquinquira campus. It is configured as an approach to teaching and learning organizational control, and applies a style that goes beyond traditional approaches to education.In this didactic unit, relevant elements in the training were considered, such as students’ previous knowledge and personal experiences, essential knowledge in the teaching-learning process. This is the starting point for the teacher to structure guidelines, activities and techniques to be developed in the classroom, when yielding to didactic transposition, in order to enhance critical thinking and conceptual evolution.Finally, this text gives a glimpse of the design, implementation and evaluation of a didactic unit of organizational control, which arises from the previous ideas of the population under study, students of the Public Accounting and Business Administration programs. Thus, this research calls on teachers to use new pedagogical and didactic strategies that achieve scientific knowledge and conceptual evolution in students, without ignoring cognitive methods and their application in real contexts, in order to promote lifelong learning in which the student and the